2017
DOI: 10.1021/acs.orglett.7b02275
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic Synthesis by Way of Diastereoselective Iodoacetoxylation and Transannular Amidation of 7–9-Membered Lactams

Abstract: Azacyclo- and azabicycloalkanone peptidomimetics were synthesized regio- and diastereoselectively by iodoacetoxylation and transannular amidation reactions on unsaturated lactam precursors contingent on ring size, olefin position, solvent, and hypervalent iodine(III) reagent. 4-Iodopyrrolizidinone 1, 7-iodoindolizidinone 2, and 4-iodo-5-acetoxylactams (e.g., 6 and 7) were made stereospecifically from 7-9-membered olefins 16, iodine, and hypervalent iodine(III) in acetonitrile or toluene, respectively. X-ray cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…16 In the case of 8-membered lactams, as well as certain 9-membered lactams, employment of hypervalent iodine [e.g., (diacetoxyiodo)benzene, DIB] in the iodo lactamization conditions in acetonitrile provided access to pyrrolizidinones and (2S,6S,7R,8S)-I 9 aa 20b (PG = Fmoc). 17 Intrigued by the role of hypervalent iodine in halo aminations of unsaturated olefins, 20 the transannular amidation of 9-membered unsaturated lactams possessing different amine protection has now been examined to develop stereoselective routes to I 2 aa and I 9 aa diastereomers 12 and 13 by way of a common lactam precursor (e.g., 11). Furthermore, with the interest in side chain mimicry, methods to introduce substituents onto the I 2 aa and I 9 aa ring systems have been developed featuring iodide elimination followed by arylation under Heck conditions and allylic oxidation of olefin intermediates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In the case of 8-membered lactams, as well as certain 9-membered lactams, employment of hypervalent iodine [e.g., (diacetoxyiodo)benzene, DIB] in the iodo lactamization conditions in acetonitrile provided access to pyrrolizidinones and (2S,6S,7R,8S)-I 9 aa 20b (PG = Fmoc). 17 Intrigued by the role of hypervalent iodine in halo aminations of unsaturated olefins, 20 the transannular amidation of 9-membered unsaturated lactams possessing different amine protection has now been examined to develop stereoselective routes to I 2 aa and I 9 aa diastereomers 12 and 13 by way of a common lactam precursor (e.g., 11). Furthermore, with the interest in side chain mimicry, methods to introduce substituents onto the I 2 aa and I 9 aa ring systems have been developed featuring iodide elimination followed by arylation under Heck conditions and allylic oxidation of olefin intermediates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With the goal of preparing multiple systems from a common strategy, the ring closing metathesis–transannular cyclization (RCM-TC) approach to azabicyclo­[ X . Y .0]­alkanone amino acids has unambiguously provided 5,5-, 5,6-, 6,5-, 6,4-, 6,6-, and 7,5-fused bicycles by way of a shared synthetic route featuring diastereoselective iodo lactamization of various 8–10-membered unsaturated lactams. Moreover, S N 1 displacement of the iodide from the resulting 7,5-bicyclic product has given access to a series of ring substituents to mimic different side chains …”
Section: Introductionmentioning
confidence: 99%
“…Iodoacetoxylation in THF of 38 to azacyclo-alkanone scaffolds 39 was then performed then used for the preparation of peptidomimetics 40. [35] The combination of NMR spectroscopy and X-ray crystallography showed that peptides 40 could serve as β-turn type mimics.…”
Section: Delta Aasmentioning
confidence: 99%
“… , These dipeptide mimetics can restrict the geometry of the peptide backbone and maintain the active conformations of the peptides in binding to their target proteins and therefore have been extensively used in many drug discovery projects, such as thrombin inhibitors, stat3 inhibitors, CCK receptor ligands, integrin receptor ligands, prostaglandin F2α (PGF2α) modulators, and Smac mimetics (Figure ). Because of their extensive applications, many synthetic methods for the synthesis of this class of compounds and their analogues have been reported, ,, and the development of more general and efficient methods which can be used to expand the diversity of the structure has always been actively pursued by organic chemists and medicinal chemists. , In this note, we report a general and efficient method for the synthesis of dipeptide mimetics with azabicyclo­[4,3,0]­nonanone and azabicyclo­[5,3,0]­decanone scaffolds.…”
mentioning
confidence: 99%
“…Because of their extensive applications, many synthetic methods for the synthesis of this class of compounds and their analogues have been reported, 1,2,6−11 and the development of more general and efficient methods which can be used to expand the diversity of the structure has always been actively pursued by organic chemists and medicinal chemists. 12,13 In this note, we report a general and efficient method for the synthesis of dipeptide mimetics with azabicyclo[4,3,0]nonanone and azabicyclo [5,3,0]decanone scaffolds.…”
mentioning
confidence: 99%